Protein directed evolution - Laos, Roberto (Pontificia Universidad Católica del Perú, 2008)
Directed evolution allows us to explore protein functionalities not required in the natural environment. It mimics natural genetic processes and selective pressures. This approach is used when the molecular basis is not completely understood and rational design is a difficult task. This approach consists of serial cycles of consecutive diversification and selection which eventually lead to the accumulation of beneficial mutations. Here are presented two cases where directed evolution is used to modify two different proteins: Taq polymerase, enzyme used for DNA extension in PCR, and the LacI repressor protein which regulates gene expression on E.coli.

Evolución dirigida de proteínas: La evolución dirigida es una técnica que nos permite explorar funciones enzimáticas que no son requeridas en el ambiente natural. Esta técnica, simula procesos genéticos naturales y de selección. Esta estrategia se utiliza cuando un diseño racional es muy complicado. Consiste en una repetición de ciclos de diversificación y selección que llevan a la acumulación de mutaciones benéficas. Aquí se presenta dos ejemplos de evolución dirigida con los cuales se ha trabajado directamente: la ADN polimerasa del organismo  Thermus aquaticus usada comúnmente en PCR, y la proteína LacI que regula la expresión de genes usados para el metabolismo de lactosa en E. Coli.
Keywords: Directed Evolution; Water In Oil Emulsions; Taq Polymerase; Lac Repressor; Pcr; Error Prone Pcr; Compartmentalized Self Replication (csr); Artificially Expanded Genetic Information System (aegis); https://purl.org/pe-repo/ocde/ford#1.04.00